2009
DOI: 10.1212/wnl.0b013e3181a92b96
|View full text |Cite
|
Sign up to set email alerts
|

Effect of statins on clinical and molecular responses to intramuscular interferon beta-1a

Abstract: Background:Findings from a small clinical study suggested that statins may counteract the ther-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 11 publications
0
38
0
Order By: Relevance
“…In a study of 30 MS patients, the treatment with simvastatin resulted in a significant reduction in the number and volume of contrastenhancing lesions, on serial monthly MRI [28]. A posthoc analysis of the interferon beta treated control arm of the SENTINEL study did not show any effect of statins on the following endpoints: adjusted annualized relapse rate, disability progression, number of contrastenhancing lesions and number of new or enlarging T2-hyperintense lesions over 2 years [31]. The STAyCIS study tried to assess the effect of statin treatment in slowing the conversion of clinical isolated syndromes to clinically definite MS, but it did not meet its primary endpoint (development of 3 or more new T2 lesions or 1 clinical relapse within 12 months) [32].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a study of 30 MS patients, the treatment with simvastatin resulted in a significant reduction in the number and volume of contrastenhancing lesions, on serial monthly MRI [28]. A posthoc analysis of the interferon beta treated control arm of the SENTINEL study did not show any effect of statins on the following endpoints: adjusted annualized relapse rate, disability progression, number of contrastenhancing lesions and number of new or enlarging T2-hyperintense lesions over 2 years [31]. The STAyCIS study tried to assess the effect of statin treatment in slowing the conversion of clinical isolated syndromes to clinically definite MS, but it did not meet its primary endpoint (development of 3 or more new T2 lesions or 1 clinical relapse within 12 months) [32].…”
Section: Discussionmentioning
confidence: 96%
“…Still, only 1 patient was under treatment with a statin, excluding the possible and meaningful interference of this kind of drugs in our results. Some studies of statin treatment in MS were performed, but they originated mixed results [28][29][30][31][32][33]. In a study of 30 MS patients, the treatment with simvastatin resulted in a significant reduction in the number and volume of contrastenhancing lesions, on serial monthly MRI [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, results of recent studies with combined therapy with IFN-b and statins are controversial. Both beneficial and harmful results of combined therapy were reported (Birnbaum et al 2008;Paul et al 2008;Rudick et al 2009). …”
Section: Discussionmentioning
confidence: 97%
“…These observations provide a rationale to evaluate the efficacy of statins administered alone or combined with approved treatments for MS. At present only a few studies, enrolling a limited number of participants, showed that lovastatin or simvastatin decreased the relapses and the number and volume of gadoliniumenhanced lesions in relapsing-remitting MS (Sena et al, 2003;Vollmer et al, 2004). More recent studies provide contrasting results about reduction or progression of relapses in patients with relapsing-remitting MS (Birnbaum et al, 2008;Rudick et al, 2009). Aimed to investigate the effects of statin-treatment combined to IFN␤-1a in MS, at least six clinical trials are still ongoing (Kamm et al, 2009;Wang et al, 2010a), but results are incomplete; therefore, no sufficient information support mono or combination therapy with statins in MS.…”
Section: G Statins and Nervous Systemmentioning
confidence: 99%